Droplet-Based Measurements of DNA-Templated Nanoclusters—Towards Point-of-Care Applications - Jonas Kluitmann; Stefano Di Fiore; Greta Nölke; Klaus Stefan Drese (Biosensors)
In this work, we investigate the fundamental usability of fluorescent DNA-templated silver nanoclusters (DNA-AgNCs) as sensors for Point-of Care-Testing (PoCT) applications. We developed a microfluidic platform for the generation of droplets containing DNA-AgNCs in defined, different chemical environments. The droplets are read out fluorescently at two different emission wavelengths. For the pre-evaluation for the usage of biologically relevant matrices with DNA-AgNCs, the response of two different DNA-AgNCs to a variation in pH and sodium chloride concentration was acquired. Our compact and simple setup can detect DNA-AgNCs well below 100 nM and allows the characterization of the fluorescence response of DNA-based biohybrid nanosensors to changes in the chemical environment within short measurement times. The model DNA-AgNCs remain fluorescent throughout the physiologically relevant chloride concentrations and up to 150 mM. Upon shifts in pH, the DNA-AgNCs showed a complex fluorescence intensity response. The model DNA-AgNCs differ strongly in their response characteristics to the applied changes in their environments. With our work, we show the feasibility of the use of DNA-AgNCs as sensors in a simple microfluidic setup that can be used as a building block for PoCT applications while highlighting challenges in their adaption for use with biologically relevant matrices.